2022
DOI: 10.1177/10732748221082372
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer in the Caribbean: A Baseline Assessment of Current Practices and Potential Needs

Abstract: Afro-Caribbean men have a higher risk of prostate cancer than any other population of men in the world. However, the Caribbean is composed of a heterogenous group of healthcare systems located on small islands which makes population-based studies difficult to conduct and interpret. The aim of this review is to compile previously published data on the state of prostate cancer in Caribbean men and to highlight potential healthcare needs that can be addressed by public health efforts. We reviewed three databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, they are also highly ranked in terms of mortality rates for men with prostate cancer [ 23 , 24 ], which might be because of overdiagnosis of prostate cancer and high life expectancy in these countries. The high rates of prostate cancer mortality among Caribbean men are likely attributed to a combination of genetic predisposition and low socioeconomic status [ 25 ]. The second class, which included approximately 58% of the study sample, had the lowest mortality rate in the initial stage and an increasing trend over the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are also highly ranked in terms of mortality rates for men with prostate cancer [ 23 , 24 ], which might be because of overdiagnosis of prostate cancer and high life expectancy in these countries. The high rates of prostate cancer mortality among Caribbean men are likely attributed to a combination of genetic predisposition and low socioeconomic status [ 25 ]. The second class, which included approximately 58% of the study sample, had the lowest mortality rate in the initial stage and an increasing trend over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be due to a combination of genetic, environmental, and lifestyle factors. [ 25 , 27 ]. The class number four had the second highest prostate cancer mortality rate at the starting point of the study, followed by an almost stable pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining prostate cancer trends in the Caribbean showed increasing or constant high prostate cancer incidence rates up to 2008 10,22–24 . Further, there remains a lack of clear, consistent guidelines related to prostate cancer screening in the Caribbean 25 . However, it is possible that changes in screening recommendations may influence the practices of healthcare providers in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…10,[22][23][24] Further, there remains a lack of clear, consistent guidelines related to prostate cancer screening in the Caribbean. 25 However, it is possible that changes in screening recommendations may influence the practices of healthcare providers in other countries. To our knowledge, there have been no studies assessing trends in prostate cancer incidence and advanced disease among men of the African Diaspora (United States and Caribbean) during the period of critical decisions about screening recommendations (since 2008).…”
mentioning
confidence: 99%
“…Statistical analysis of the variables demonstrated a significant moderate correlation between PSA and Gleason score. Another study conducted in Jamaica by Shirley et al[43] investigated 99 PC patients' biopsy clinicopathology findings from 1993 to 1997 in the Pathology Department at the University of the West Indies (UWI). It was reported that the median PSA was 37 ng/ml, 63% of the patients clinically had stage T1 or T2 illness, and 60% of PC cases had a Gleason score of 8-10.…”
mentioning
confidence: 99%